The Business Model Canvas Development with an Importance-Performance Mapping Analysis (A Case of Svarga Healthy Food) - Kresna Audito; Marine Novita; Andreas Chandra Santoso; Ferdi Antonio (Budapest International Research and Critics University, 2022)
In order to develop Business Model Canvas (BMC) (Osterwalder, et al., 2013) and test the value proposition to the potential customer, this study aimed to analyze the set of customer perceived values on purchase decision making in the context of healthy food. This study was carried out as quantitative with a survey and data were taken purposively according to criteria that meet the customer segmentation. Data were obtained from 102 samples who priorly have informed of the product and service provided by Swarga Healing Food one of the healthy food providers that are about to enter the market. Data was collected through an online questionnaire with a Likert scale of 1 to 6 points. Data is analyzed through the PLS-SEM method and use importance-performance mapping (IPMA) calculation to identify items that are most important from the customer perspective. The result of the study demonstrated a reliable and valid measurement to assess the effect on the purchase decision. The finding revealed that indicator from variety value is the most influential in the customer decisions followed by emotional value, food quality value, and healthy value. These findings were utilized to propose a new BMC with a more relevant value proposition.